Oscillation criteria fora forced superlinearconformable fractional differential equation with damping term (2020)
In this paper we establish some new oscillation criteria for the solution of a forced superlinear conformable fractional differential equation with damping term by using the averaging functions method. Our results provide extensions and improvement to some existing ones. Some examples are also given to show the relevance of our results.